Current Perspectives in Contaminant Hydrology and Water Resources Sustainability - Bradley, Paul M. (IntechOpen, 2013)
Human society depends on liquid freshwater resources to meet drinking, sanitation and hygiene, agriculture, and industry needs. Improved resource monitoring and better understanding of the anthropogenic threats to freshwater environments are critical to efficient management of freshwater resources and ultimately to the survival and quality of life of the global human population. This book helps address the need for improved freshwater resource monitoring and threat assessment by presenting current reviews and case studies focused on the fate and transport of contaminants in the environment and on the sustainability of groundwater and surface-water resources around the world. It is intended for students and professionals working in hydrology and water resources management.